Indications for caesarean sections at ≥34 weeks among nulliparous women and differential composite maternal and neonatal morbidity. (10th February 2014) - Chauhan, SP; Beydoun, H; Hammad, IA; Babbar, S; Hill, JB; Mlynarczyk, M; D'Alton, ME; Abuhamad, AZ; Vintzileos, AM; Ananth, CV
<x xml:space="preserve">Abstract</x> Objective To compare composite maternal and neonatal morbidities (CMM, CNM) among nulliparous women with primary indications for caesarean section (CS) as acute clinical emergency (group I; ACE), non‐reassuring fetal heart rate (group II) and arrest disorder (group III). Design A multicentre prospective study. Setting Nineteen academic centres in the USA, with deliveries in 1999–2002. Population Nulliparous women (n = 9829) that had CS. Methods Nulliparous women undergoing CS for three categories of indications were compared using logistic regression model, adjusted for five variables. Main outcome measures CMM was defined as the presence of any of the following: intrapartum or postpartum transfusion, uterine rupture, hysterectomy, cystotomy, ureteral or bowel injury or death; CNM was defined as the presence of any of the following: umbilical arterial pH <7.00, neonatal seizure, cardiac, hepatic, renal dysfunction, hypoxic ischaemic encephalopathy or neonatal death. Results The primary reasons for CS were ACE in 1% (group I, n = 114) non‐reassuring FHR in 29% (group II; n = 2822) and failed induction/dystocia in the remaining 70% (group III; n = 6893). The overall risks of CMM and CNM were 2.5% (95% confidence intervals, CI, 2.2–2.8%) and 1.9% (95% CI 1.7–2.2), respectively. The risk of CMM was higher in group I than in group II (RR 4.1, 95% CI 3.1, 5.3), and group III (RR 3.2, 95% CI 2.7, 3.7). The risk of CNM was also higher in group I than in group II (RR 2.8, 95% CI 2.3, 3.4) and group III (RR 14.1, 95% CI 10.7, 18.7). Conclusions Nulliparous women who have acute clinically emergent caesarean sections are at the highest risks of both composite maternal and neonatal morbidity and mortality.